2013
DOI: 10.1016/j.apsusc.2012.12.156
|View full text |Cite
|
Sign up to set email alerts
|

Growth of silver on ZnO and SnO2 thin films intended for low emissivity applications

Abstract: In the present work we have investigated the relationships existing between the optical properties and the growth mechanism, microstructure and surface roughness of SnO 2 and ZnO oxide films prepared by magnetron sputtering under conditions resembling those utilized in industry. Thin films of these oxides with different thicknesses were characterized by atomic force microscopy, glancing incidence X-ray diffraction (GIXRD), X-ray reflectometry and spectroscopic Ellipsometry. The roughness evolution of the film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Among them, the substrates are undoubtedly important factors because they are related directly to the interaction of Ag atom with that of the substrate [24] and the nucleation and grain growth behavior of Ag layer [25][26][27][28]. In an earlier report [19], it was found that the spreading of Ag on the surface of ZnO was better than that on SnO 2 due to a better affinity between Ag and ZnO though surface of ZnO was rougher than that of the latter. It brings about a question whether there exists any difference between the spreading of Ag on the surface of ZnO and that on ITO.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among them, the substrates are undoubtedly important factors because they are related directly to the interaction of Ag atom with that of the substrate [24] and the nucleation and grain growth behavior of Ag layer [25][26][27][28]. In an earlier report [19], it was found that the spreading of Ag on the surface of ZnO was better than that on SnO 2 due to a better affinity between Ag and ZnO though surface of ZnO was rougher than that of the latter. It brings about a question whether there exists any difference between the spreading of Ag on the surface of ZnO and that on ITO.…”
Section: Introductionmentioning
confidence: 97%
“…With increasing the thickness of Ag layer, the sheet resistance of the Ag/AZO bilayer reduces and is even lower than that of the Ag/ITO bilayer. The reason may be related to the spreadability [19,24] of the Ag layer on the AZO underlayer. As shown in Figure 3, the Ag layer deposited on the AZO has a better spreadability.…”
Section: Spreadability Of Ag On Underlayersmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-layer glazing separated by air, vacuum, inert gas or transparent insulators such as silicon aerogel [7]reduce thermal losses. Tinted or reflective glazing technologies [8][9][10], low emissivity coatings [10,11] and spectrally selective glazing [10][11][12] regulate the spectral response of the window. Switchable glazing technologies such as electrochromic [13][14][15], thermochromic [15,16] or photochromic glazing and liquid crystals [17] have been developed as part of 'smart' fenestration systems to provide varying levels of daylighting and passive thermal control for the interior.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO/SnO 2 (ZS) is one of the most important TCO materials. It has numerous applications in modern technologies due to its attractive properties such as wide band gap, high electrical conductivity, high transmittance in the ultraviolet-visible (UV-Vis) region, high infrared (IR) reflectance, and its abundance in nature [3]. Quantum dots (QDs) based semiconducting materials are beneficial due to their unique optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%